Interorgan and Transcellular Communication in Metabolic Disease: Insights From Recent CMGH Studies - Tien S. Dong; Emeran Mayer (Cellular and Molecular Gastroenterology and Hepatology)
The emergence of interorgan and transcellular signaling as a defining hallmark of metabolic disease has catalyzed a paradigm shift in gastroenterology and hepatology. Increasingly, the gut, liver, adipose tissue, immune system, and the nervous system are being understood as nodes in an integrated metabolic network rather than isolated organs. The gut microbiome and its metabolites, enteroendocrine signaling, bile acid regulation, and epithelial barrier functions now occupy center stage in dissecting the pathophysiology not only of gastroenterologic conditions, such as obesity, metabolic dysfunction-associated steatotic liver disease, and cirrhosis, but also of several disorders making up the chronic noncontagious disease epidemic.This paradigm shift is being driven by advances in molecular biology, systems biology, and computational modeling, which have enabled a holistic understanding of how communication between organs orchestrates metabolic homeostasis.1 Key to this understanding is the realization that local perturbations in 1 organ, such as gut microbial dysbiosis, can have systemic repercussions that affect distant organs, such as the liver or brain.2,3 This has redefined how researchers conceptualize disease progression and therapeutic interventions. Rather than focusing on a single tissue, there is increasing interest in identifying molecular messengers that mediate crosstalk between organ systems, such as microbial metabolites, enteroendocrine peptides, bile acids, and cytokines.In this review, we highlight 4 recent and impactful studies published in Cellular and Molecular Gastroenterology and Hepatology that exemplify these advances. Each study offers a unique window into the mechanisms by which gut-derived signals influence host metabolism and disease states. Together, they deepen the understanding of the complex dialogue between organs and open new avenues for therapeutic exploration. We conclude by discussing the implications of these findings and outlining emerging questions and future directions for the field.